Subcritical CO2 extraction of a volatile oil-rich fraction from the seeds of Nigella sativa for potential pharmaceutical and nutraceutical applications. Issue 2 (4th March 2018) - Edris, Amr E.; Wawrzyniak, Paweł; Kalemba, Danuta
Abstract: Seeds of black cumin ( Nigella sativa L.) were subjected to subcritical CO2 extraction (SbFE) at 70 bar and 30 °C for 2 h in a trial to isolate a volatile oil-rich fraction. That treatment led to obtaining an oleoresin which constituted 1.74 wt.% of the total seeds' weight and was found to be rich in its volatile oil content (66.6 wt.%). Traditional methods of extracting the oleoresin using n-hexane at room temperature or at 60 °C led to much higher yields (23.6 and 32.9 wt.%), respectively. The volatile oils' content of these oleoresins was 4.75 and 3.59 wt.%. GC-MS analysis showed that the volatile oil obtained after SbFE is characterized by the highest thymoquinone (TQ) content (60.5%) compared to that obtained after hexane extraction at room temperature (37.6%) or at 60 °C (41.6%). On the other hand, TQ content of the volatile oils isolated directly from the seeds by hydrodistillation and steam distillation was much lower (10.2 and 23.7%), respectively. Based on the above mentioned, SbFE of N. sativa seeds was found to be a useful green tool for obtaining a volatile oil-rich oleoresin with high TQ percentage which can be applied in pharmaceutical and nutraceutical products.